CHANGES IN THE VIRTUE BUSINESS PRACTICES OF THE PANDEMIC OF COVID-19: analysis of transformations in a construction company in Araraquara/SP - Martins de Oliveira, Kássia Suellen; Del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
The outbreak of the new coronavirus (COVID-19) in 2020 is causing countless transformations to business practices, which must adapt and even reinvent themselves in the face of a scenario of social isolation, uncertainty and new commercial practices. Put in this way, this study aims to analyze the importance of being attentive to changes in the business environment, and how the pandemic is making companies in different sectors rethink their practices and in offering products and services. To demonstrate these concepts in practice, the study presents an exploratory research, through in-depth interviews with administrators of a construction company in the city of Araraquara / SP, in order to better understand the impacts of social isolation and the new government rules of trade, and how this company is adapting to overcome the crisis. What can be seen from this study is that the new coronavirus brings with it a sudden need to rethink in every aspect of the business, not exactly to continue to grow and prosper, but fundamentally to survive and continue to operate in a market that is constantly changing.